Pengaruh Strategi Pengisian Daya Terhadap Kenaikan Beban Puncak Akibat Penetrasi Kendaraan Listrik - Boy Ihsan; Deny Hamdani; Nanang Hariyanto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
To overcome the problem of energy crisis and global warming, many countries in the world are pushing growth in the use of electric vehicles. In the future, the use of electric vehicles in large numbers will also occur in Indonesia and charging electric vehicles will become a new load on the electricity system. One of the effects of electric vehicle penetration is an increase in the system's peak load. Therefore, this study examines how the increase in daily load due to penetration of electric vehicles and how the strategy of electric vehicles charging to reduce the increase in load on one of the electricity systems in Indonesia, namely the Jawa-Bali system. The calculation results show that the Jawa-Bali electrical system is only able to accommodate electric vehicle penetration by 20% if the problem of losses, instability, and line loading are ignored. In the case of 10% penetration of electric vehicles, the peak load of the Jawa-Bali system increased by 5,857 MW. However, by scheduling electric vehicle charging, the increase in peak load can be reduced by 3,232 MW and by using the V2G scheme, the energy supplied by the system generator can be reduced by 20,003 MWh.